2021
DOI: 10.1371/journal.ppat.1009448
|View full text |Cite
|
Sign up to set email alerts
|

Extensive activation, tissue trafficking, turnover and functional impairment of NK cells in COVID-19 patients at disease onset associates with subsequent disease severity

Abstract: The SARS-CoV-2 infection causes severe respiratory involvement (COVID-19) in 5–20% of patients through initial immune derangement, followed by intense cytokine production and vascular leakage. Evidence of immune involvement point to the participation of T, B, and NK cells in the lack of control of virus replication leading to COVID-19. NK cells contribute to early phases of virus control and to the regulation of adaptive responses. The precise mechanism of NK cell dysregulation is poorly understood, with littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 53 publications
7
44
0
1
Order By: Relevance
“…Although the vaccines were inactivated, they still triggered cellular immune responses after vaccination, including increases of T, Ts, and NK cells. Earlier studies on COVID-19 infections confirmed that virus invasion induces innate immunity [ 19 ]. In studies of mRNA vaccines, BNT162b1 stimulates strong CD4+ T cell and CD8+ T cell responses and strong antibody responses [ 20 ].…”
Section: Discussionmentioning
confidence: 98%
“…Although the vaccines were inactivated, they still triggered cellular immune responses after vaccination, including increases of T, Ts, and NK cells. Earlier studies on COVID-19 infections confirmed that virus invasion induces innate immunity [ 19 ]. In studies of mRNA vaccines, BNT162b1 stimulates strong CD4+ T cell and CD8+ T cell responses and strong antibody responses [ 20 ].…”
Section: Discussionmentioning
confidence: 98%
“…The asymptomatic biosignature also involved increased numbers of CD56 hi CD16 − NK cells and a clonal expansion of CD4 + T cell populations. By contrast, symptomatic, acute infection involved a reduction in the number of CD56 hi NK cells and an increased number of CD56 low NK cells 49 . As CD56 hi CD16 − NK cells are the subset associated with cytokine production rather than cytotoxicity, these findings may suggest a regulatory function for NK cell cytokines in asymptomatic disease.…”
Section: Immunity After Asymptomatic Primingmentioning
confidence: 89%
“…Limited research on the NK cell derangement during SARS-CoV-2 infection demonstrate that patients suffering from COVID-19 have an increased amount of NK and CD8+T cells with an exhausted phenotype and high expression of the inhibitory receptor, NKG2A [164]. Increased proportions of NK cells expressing activating receptors (NKG2D+, NKG2C+) were found to be protective against the worst outcome, characterized by need for mechanical ventilation [165]. IL-6, that is present in elevated levels in sera of patients with COVID-19 [166], may downreg-ulate NKG2D on NK cells, leading to impairment of NK activity [167].…”
Section: Nkg2d and Its Role In Sars-cov-2 Infectionmentioning
confidence: 99%